An empirical study on the effects of taking less credit hours on the performance of UiTM Sarawak's probation students / Mariam Rahmat, Susan Hydra Sikayu and Azura Ahmad - Rahmat, Mariam; Sikayu, Susan Hydra; Ahmad, Azura (Universiti Teknologi Mara Shah Alam, Selangor, 2009)
Poor academic performance has been one of the many critical issues faced by the higher learning institutions. Measures in the form of support systems have been found productive in improving the academic performance and retaining an educationally at risk students. This study investigates the performance of UiTM Sarawak students placed under first and second probation known as PI and P2 respectively after they had taken 12 hours of maximum credit hours as stated in the Peraturan Akademik UiTM (Pindaan 2008) (UiTM Academic Regulation). The sample for this study was taken from the results of Diploma in Accounting (DIA), Diploma in Business Studies (DBS), Diploma in Banking (DIB), Diploma in Public Administration (DPA) and Diploma in Office Management (DOM) students in UiTM Sarawak. The results of students under PI and P2 status accumulated from March 2002 until October 2006 were analyzed. The overall performance of PI students were not encouraging as only less than 40% managed to achieve a minimum satisfactory 2.00 of CGPA. In their second attempt, their performance was still far from satisfactory. P2 students have recorded the highest dismissal rate with more than 50% of P2 students from all faculties being dismissed. The graduating rate for PI students has not been promising either as all programs recorded less than 10% graduating rate. Probation students who had acquired a CGPA of 1.92 were found to improve their performance to a satisfactory level of CGPA 2.00, while those with CGPA below 1.92 did not do so. Results from this study might be useful for both students and UiTM Sarawak, in taking aggressive actions to improve the performance of these students should their CGPA fall below 1.92.